Achieving compatibility in blends of low-density polyethylene/polyamide-6 with addition of ethylene vinyl acetate - TAŞDEMİR, MÜNİR (My University, 2001)
Polymer alloys and blends, whose major advantage is the potential of achieving a range of physical and mechanical properties, have continued to be a subject of interest over recent years. Addition of a block or graft copolymer, with chemically similar segments to those involved in the polymer blend considered, led to a variety of desirable properties. The copolymer added to the blend functioned to promote a homogeneous dispersion of the constituent phases and to enhance their mutual adhesion. Such agents that enable better dispersion in polymer blends are known as compatibilizers. In this study an attempt has been made to improve the compatibility in a polymer blend composed of two normally incompatible constituents, LDPE and PA6, by addition of a compatibilizer. The compatibilizer agent, ethylene vinyl acetate (EVA), was added to the polymer blend in ratios of 1, 5, and 10% by using a twin-screw extruder. The effect of EVA on the crystallization of the polymer constituents was observed through DSC examinations. Furthermore, the control sample and all three blends of LDPE/PA6/EVA were subjected to examinations to obtain their yield and tensile strengths, elasticity modulus, percentage elongation, izod impact strength, hardnèss, and melt flow index. © 2001 John Wiley & Sons, Inc. J Appl Polym Sci.
Keywords: Compatibilizer; Polymer alloys; Polymer blends